Evaluasi Supplier Dengan Menggunakan Metode Analytical Hierarchy Process Dan Taguchi Loss Function - Muhammad Yanu Asdidi; Moeso Alpianto; Ahmad Ainul Yaqin (Jurnal Teknik Industri, 2018)
Supplier evaluation process is a strategic activity on purchasing management that aims to find out the performance of the supplier. PT. Fronte Classic Indonesia is a company manufacturing car carpet, one of the raw materials needed in producing car carpet that is calcium. The supplier in partnership with the company has performance that is less suitable. The methods used in this research Analytical Hierarchy Process (AHP) and Taguchi Loss Function. AHP is used to determine the weights of the criteria and Taguchi Loss Function is used to calculate the loss function of the respective supplier. Supplier evaluation process carried out to search for suppliers and meet the criteria of the company. The criteria used in the evaluation of suppliers are price, delivery, quality, the accuracy of goods quantity, guarantee policy, response to claims. The results showed that the suppliers who meet the criteria of the company by providing minimum losses as the best supplier.